Scapular Chondrosarcoma (Revista de Medicina Clinica, 2024)
Clinical snapshot on "Scapular Chondrosarcoma" presented in Volume 8  Issue 2 of Revista de Medicina Clínica
Keywords: Scapular Chondrosarcoma; Case report; Clinical snapshot